Empathy and Its Discontents. Issue 1 (January 2017) - Bloom, Paul
Abstract : What role does the experience of feeling what you think others are feeling – often known as 'empathy' – have in moral deliberation and moral action? Empathy has many fans and there is abundant evidence that it can motivate prosocial behavior. However, empathy is narrow in its focus, rendering it innumerate and subject to bias. It can motivate cruelty and aggression and lead to burnout and exhaustion. Compassion is distinct from empathy in its neural instantiation and its behavioral consequences and is a better prod to moral action, particularly in the modern world we live in. Trends: The act of experiencing what you believe others are experiencing – sometimes known as 'empathy' – is often viewed as having positive effects, motivating kindness and inhibiting aggression. In support of this, the experience of empathic distress increases the likelihood of prosocial action toward a suffering individual. Empathy has serious limitations, however, particularly when it comes to moral decision-making in the modern world. Both laboratory studies and examples from everyday life suggest that it leads to biased and innumerate decisions – choices that clash with our considered moral judgments. Also, while empathy can motivate kindness, it can also spur cruel and irrational actions, including atrocities and war. There are alternatives to empathy. In particular, compassion – in the sense of valuing other people and caring about their welfare but without necessarily feeling their pain – may have all the advantages of empathy and few of its weaknesses.